Cardiopulmonary resuscitation in low-resource settings: a statement by the International Liaison Committee on Resuscitation, supported by the AFEM, EUSEM, IFEM, and IFRC - Schnaubelt, Sebastian; Garg, Rakesh; Atiq, Huba; Baig, Noor; Bernardino, Marta; Bigham, Blair; Dickson, Samantha; Geduld, Heike; Al-Hilali, Zehra’; Karki, Sanjaya; Lahri, Sa’ad; Maconochie, Ian; et al. (The Lancet Global Health, 2023)
Most recommendations on cardiopulmonary resuscitation were developed from the perspective of high-resource settings with the aim of applying them in these settings. These so-called international guidelines are often not applicable in low-resource settings. Organisations including the International Liaison Committee on Resuscitation (ILCOR) have not sufficiently addressed this problem. We formed a collaborative group of experts from various settings including low-income, middle-income, and high-income countries, and conducted a prospective, multiphase consensus process to formulate this ILCOR Task Force statement. We highlight the discrepancy between current cardiopulmonary resuscitation guidelines and their applicability in low-resource settings. Successful existing initiatives such as the Helping Babies Breathe programme and the WHO Emergency Care Systems Framework are acknowledged. The concept of the chainmail of survival as an adaptive approach towards a framework of resuscitation, the potential enablers of and barriers to this framework, and gaps in the knowledge are discussed, focusing on low-resource settings. Action points are proposed, which might be expanded into future recommendations and suggestions, addressing a large diversity of addressees from caregivers to stakeholders. This statement serves as a stepping-stone to developing a truly global approach to guide resuscitation care and science, including in health-care systems worldwide.
Keywords: Cardiopulmonary resuscitation; AFEM; EUSEM; IFEM; IFRC